GSAP modulates γ-secretase specificity by inducing conformational change in PS1 - Wong, Eitan (Proc Natl Acad Sci U S A, 2019)
The mechanism by which γ-secretase activating protein (GSAP) regulates γ-secretase activity has not yet been elucidated. Here, we show that knockout of GSAP in cultured cells directly reduces γ-secretase activity for Aβ production, but not for Notch1 cleavage, suggesting that GSAP may induce a conformational change contributing to the specificity of γ-secretase. Furthermore, using an active-site–directed photoprobe with double cross-linking moieties, we demonstrate that GSAP modifies the orientation and/or distance of the PS1 N-terminal fragment and the PS1 C-terminal fragment, a region containing the active site of γ-secretase. This work offers insight into how GSAP regulates γ-secretase specificity.